The grim grotto [compact disc, unabridged] - Snicket, Lemony (Snicket, Lemony. Series of unfortunate events, 2004)
The Baudelaire siblings descend into the depths of despair, underwater. The horrors they encounter are too numerous to list, and include mushrooms, a mechanical monster, a distressing message from a lost friend, and tap dancing.